Psychiatric admission during pregnancy in women with schizophrenia who attended a specialist antenatal clinic - Elly Lorraine Harris; Jacqueline Frayne; Suzanna Allen; Kanni Renganathan; Thinh Ngoc Nguyen (Taylor & Francis Group, 2019)
Objectives: The mental health and wellbeing of pregnant women with schizophrenia is an area of research interest. We aim to explore this relationship particularly in regards to psychiatric admission rates, timing and their associated contributing factors. Methods: A total of 98 pregnancies to women with schizophrenia, who attended a specialist antenatal clinic and delivered from July 2007 to February 2016, were retrospectively examined. The cohort was divided into two groups based on psychiatric admission. Descriptive data were analyzed using SPSS software. Results: Overall, 40.8% required psychiatric admission during pregnancy. A higher proportion of subjects had their initial psychiatric admission in the first trimester compared to the third trimester (p = .002). Of note, 10.2% were admitted within one month either side of conception. Women with admission also presented later for their first antenatal appointment (p = .04, 95% CI −2.1 to −1.9). Psychiatric admission was associated with substance (p = .014) and alcohol use (p = .001), child protective services involvement (p = .022) and infant being placed in out-of-home care (p = .01), but not with poorer obstetric or neonatal outcomes. Conclusion: High rates of psychiatric admission are evident throughout pregnancy for women with schizophrenia, with a high proportion of first presentations for admission occurring in the first trimester. Psychiatric admission is associated with poorer antenatal care attendance and adverse psychosocial outcomes, highlighting the need for enhanced multidisciplinary pregnancy care for this at risk group. Inpatient psychiatric services should consider pregnancy testing and contraception review for all women of childbearing age, admitted with schizophrenia.